COGNITION-GUIDE – Genomics-Guided Targeted Post-Neoadjuvant Therapy in Patients with Early Breast Cancer: Study Design of a Multicenter, Open-Label, Umbrella Phase II Study - Pixberg, Constantin; Maurer, Christian; Smetanay, Katharina; Straßl, Luise; Hlevnjak, Mario; Zapatka, Marc; Wagner, Celina V.; Yazdanparast, Haniyeh; Kurzawa, Johanna; Erben, Vanessa; Feng, Fangyoumin; Hong, Chen; Hübschmann, Daniel; Buschhorn, Lars; Suppelna, Jan Philip; Michel, Laura; Heublein, Sabine; Fremd, Carlo; Zivanovic, Oliver; Sinn, Peter; Stenzinger, Albrecht; Haidinger, Renate; Schumacher-Wulf, Eva; Ditsch, Nina; Loibl, Sibylle; Fröhling, Stefan; Link, Theresa; Wimberger, Pauline; Blohmer, Jens-Uwe; Huebner, Hanna; Fasching, Peter A.; Janni, Wolfgang; Schlenk, Richard F.; Thewes, Verena; Lichter, Peter; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2025)
As part of the COGNITION diagnostic registry program, residual tumor material after neoadjuvant therapy (NAT) of patients with early breast cancer (eBC), who are still at high-risk for relapse after NAT, is analyzed by next generation sequencing to identify biomarkers and actionable alterations. This strategy aims to stratify patients for subsequent genomics-guided therapies to reduce the significant risk of metastatic dissemination and hence to improve disease-free survival.COGNITION-GUIDE is a multicenter umbrella phase-II-trial to translate molecular biomarker profiles generated in the COGNITION platform into six molecular-guided post-neoadjuvant therapeutic options in addition to standard-of-care treatment. Patients can be allocated toThe primary endpoint is invasive disease-free survival (IDFS) four years after surgery. Secondary endpoints include IDFS in each study arm separately, distant disease-free survival, overall survival and safety. 240 patients will be enrolled within four years.The COGNITION-GUIDE trial, which was activated in June 2023 and will recruit in different centers in Germany, empowers a risk-adapted, biomarker-guided therapy escalation algorithm in eBC patients who are still at high risk of metastasis.
Keywords: precision oncology; early breast cancer; clinical trial in progress; targeted therapy